Moving toward equity: fostering transdisciplinary research between the social and behavioral sciences and implementation science to end the HIV epidemic. Issue 2 (March 2022) - Pyra, Maria; Motley, Darnell; Bouris, Alida
Abstract : Purpose of review: Since the beginning of the HIV epidemic, social and behavioral scientists have developed interventions to stem the spread of the virus. The dissemination of these interventions has traditionally been a lengthy process; however, implementation science (IS) offers a route toward hastening delivery of effective interventions. A transdisciplinary approach, wherein IS informs and is informed by social and behavioral sciences (SBS) as well as community participation, offers a strategy for more efficiently moving toward health equity and ending the HIV epidemic. Recent findings: There has been considerable growth in HIV research utilizing IS theories, methods and frameworks. Many of these studies have been multi or interdisciplinary in nature, demonstrating the ways that IS and SBS can strengthen one another. We also find areas for continued progress toward transdisciplinarity. Summary: We review literature from 2020 to 2021, exploring the ways IS and SBS have been used in tandem to develop, evaluate and disseminate HIV interventions. We highlight the interplay between disciplines and make a case for moving toward transdisciplinarity, which would yield new, integrated frameworks that can improve prevention and treatment efforts, moving us closer to achieving health equity.